A Review on Occupational Health and Safety Management - Pradhan, Bibhuti B; Mishra, Sasanka S (International Journal of Psychosocial Rehabilitation, 2019)
In reviewing the latest research on "occupational health and safety" (OHS), this paper states that the increase in the number of OHS specialists has resulted in a focus on practice and policy away from more academic concerns earlier addressed by academics in sociology and psychology disciplines. There has been a hiatus, and this is demonstrated by the lack of management studies, although OHS is progressively used as a key business organizations administrative and tactical concern. This review assesses the contributions of sociology, psychology, management studies and industrial relations, and analyses five categories of specialist OHS literature, namely: systematic OHS management; prescriptive; success-based; disaster and error based; and climate, culture, and high-reliability research. The philosophical and methodological limitations of such a professional orientation are addressed, and future research prospects are outlined, for which the writers suggest that a variety of methodological approaches be adopted by management scholars.